Nasogastric Tube Placement and Esophageal Perforation in Extremely Low Birth Weight Infants - Su-Boon Yong; Jui-Shan Ma; Feng-Shun Chen; Mei-Yung Chung; Kuender D. Yang (Elsevier, 2016)
Perforation of the esophagus associated with placement of nasogastric tubes is not uncommon in preterm infants. Herein we report three cases of iatrogenic esophageal perforation associated with nasogastric tube placement. With nonsurgical management of parenteral nutrition and broad-spectrum antimicrobial therapy, all three neonates survived without sequelae. Effective strategies to prevent such complications are discussed.